Planktonic foraminiferal biostratigraphy of the Miocene Arakawa Group in central Japan - Hiroki Hayashi; Masaki Takahashi (Revista Mexicana de Ciencias Geológicas)
We examined a planktonic foraminiferal biostratigraphy in the middle to upper Miocene Arakawa Group in central Japan. Chronostratigraphy has been already established for this sequence based on K-Ar ages of intercalated volcaniclastic layers. The studied section corresponds to planktonic foraminiferal zones N.8 to N.14 of the standard zonation. We detected fifteen biohorizons including a new one and estimated their numerical ages based on the K-Ar chronostratigraphy. The comparison of our ages with data from elsewhere suggest that four of our ages (the last occurrence of Praeorbulina sicana, the first occurrence of Orbulina suturalis, the first occurrence of Globigerina nepenthes, and the last occurrence of Neogloboquadrina mayeri) would coincide with those of the standard time scale, that is to say that these four shows better reproducibility for sites between lowand mid-latitude regions. In addition, five of those, namely, the last occurrence of Globorotalia bykovae, the last occurrence of Tenuitella clemenciae, the first occurrence of Gna. nepenthes, the last occurrence of Globorotalia ichinosekiensis, and the last occurrence of Globorotalia iwaiensis, have a good potential for correlating marine strata in Japan.